CONFIRMATORY FACTOR ANALYSIS INTELLECTUAL CAPITAL, KNOWLEDGE MANAGEMENT AND COMPETITIVE ADVANTAGE OF MSMEs - SM, Suharto; Rokhman, M. Taufiq Noor; Jamil, Ahmad (International Journal of Small and Medium Enterprises, 2021)
Micro, Small and Medium Enterprises (MSMEs) are the most important pillars in the Indonesian economy and the high number of MSMEs in Indonesia cannot be separated from the existing problems. The problems faced by MSMEs cause the low competitiveness faced by MSMEs. The competitive advantage generated by MSMEs comes from superior resources which are reflected in the company's intellectual assets (intellectual capital). SMEs that can create a competitive advantage must have different resources from their competitors. One of the resources that can be highlighted is knowledge resources. The purpose of this study is to analyze confirmatory factors intellectual capital, knowledge management and competitive advantage. Analysis of the data used in the study using confirmatory factor analysis (CFA) techniques, the results of the study show that the indicator that is considered to have the largest or strongest contribution in forming the intellectual capital variable is human capital. The indicator that is considered to have the largest or strongest contribution in forming the Knowledge Management variable is the use of knowledge and the indicator that is considered to have the largest or strongest contribution in forming the variable of competitive advantage is not easy to replace.JEL Classification Codes: O34, D83, L15, L26.